1993
DOI: 10.1021/bi00213a002
|View full text |Cite
|
Sign up to set email alerts
|

IL-1.beta. induces the coexpression of both nitric oxide synthase and cyclooxygenase by Islets of Langerhans: activation of cyclooxygenase by nitric oxide

Abstract: Autoimmune diabetes is characterized by an early infiltration of lymphocytes into and around islets, which is followed by selective destruction of the insulin-secreting beta-cell. Cytokines released during this inflammatory reaction have been implicated as effector molecules which mediate beta-cell destruction. In vitro treatment of rat islets with the cytokine IL-1 beta results in an inhibition of glucose-stimulated insulin secretion that is mediated by the overproduction of nitric oxide. IL-1 beta also stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
138
0
5

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(155 citation statements)
references
References 31 publications
(26 reference statements)
10
138
0
5
Order By: Relevance
“…Previous studies have shown that the expressions of iNOS and COX-2 are coordinately regulated in response to a number of inflammatory mediators (35)(36)(37)(38). One activator of iNOS expression by macrophages is dsRNA (10), and consistent with the previously described coordinate regulation of COX-2 and iNOS expression, dsRNA stimulates COX-2 expression by RAW 264.7 cells (Fig.…”
Section: Effects Of Dsrna and Ifn-␥ On Cox-2 Expression By Macrophagessupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies have shown that the expressions of iNOS and COX-2 are coordinately regulated in response to a number of inflammatory mediators (35)(36)(37)(38). One activator of iNOS expression by macrophages is dsRNA (10), and consistent with the previously described coordinate regulation of COX-2 and iNOS expression, dsRNA stimulates COX-2 expression by RAW 264.7 cells (Fig.…”
Section: Effects Of Dsrna and Ifn-␥ On Cox-2 Expression By Macrophagessupporting
confidence: 85%
“…Virus infection has been shown to stimulate COX-2 expression (29 -32), and inhibitors of COX-2 enzymatic activity attenuate virus replication (33,34), suggesting that the expression of COX-2 and the increased production of PGs may play an important role in viral replication. In addition, we and others have shown that under proinflammatory conditions the expression of COX-2 and iNOS appear to be coordinately regulated (35)(36)(37)(38). Using macrophages isolated from PKR Ϫ/Ϫ mice and overexpression of dnPKR, we show that the presence of functional PKR is not required for dsRNA-and EMCV-induced COX-2 expression by macrophages.…”
mentioning
confidence: 64%
“…Recently, it has been shown that COX-2 expression is also induced in the pancreatic islets under high glucose conditions (9,10). Moreover, IL-1␤ signaling stimulates COX-2 induction and PGE 2 production in pancreatic islets (12,13,18). These results, taken together, suggest that COX-2 plays a role in the IL-1␤-induced ␤-cell damage.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies in the literature indicate that NO (in the presence or absence of cytokines) enhances cyclooxygenase activity and PGE 2 production in various cell types including normal human chondrocytes (28)(29)(30)(31)(32)(33). Salvemini et al (34) have shown that injection of iNOS inhibitors into a rodent air pouch model (carrageenan-induced) blocked both iNOS and COX-2 activity in areas of inflammation.…”
Section: Discussionmentioning
confidence: 99%